PREVALENCE, FORMS AND FACTORS OF GENDER-BASED VIOLENCE AND VIOLENCE AGAINST WOMEN AND GIRLS IN CALABAR, NIGERIA - WILLIAMS, Dodeye Uduak; NYONG, Sovereign Felix (Socialscientia: Journal of Social Sciences and Humanities, 2020)
Gender-Based Violence (GBV) and Violence against Women and Girls (VAWG) has remained a serious development challenge, locally and globally. This study is part of a pilot study that is aimed at examining GBV and VAWG in Nigeria. The focus is to identify the prevalence, nature and sources of the phenomenon as well as identify some of the solutions that have been adopted as a way of curbing its prevalence. While depending on extant literature for existing theoretical and empirical data, we carry out a focus group study involving four (4) WhatsApp groups whose members live in or have lived in Calabar, Cross River State for not less than 2 years. This paper reports the findings of our initial WhatsApp focus group survey, with 14 participants. Using content analysis, we collate and analyse their responses in a descriptive format under the main themes: prevalence, forms/manifestation and factors responsible for GBV and VAWG in Nigeria. We find that GBV and VAWG is perceived by a large percentage of women as not declining, the most common forms being sexual, emotional, verbal, financial and physical violence.